Heat transfer analysis of premixed low calorific value landfill gas impinging flame under oxygen and hydrogen enrichment - Kangdong Chen; Udaya Kahangamage; Kang Tan; Chun-wah Leung (Results in Engineering)
The effective utilization of low-calorific value gases is important for meeting growing demand of energy and also addressing associated environmental concerns. In this study, the heat transfer of impinging flames of low-calorific value landfill gas (BG30) was analyzed under hydrogen and oxygen enrichment. Numerical simulations were conducted to estimate the heat transfer from the impinging flames and compared with that of the high-calorific value landfill gas (BG60) flames. The heat flux from the impinging flame was analyzed from the perspectives of Laminar Burning Velocity (LBV), temperature and velocity fields of the impinging flame using the field synergy principle. The heat transfer from impinging flame on to the target plate was categorized into heat transfer from the heat generated in the boundary layer (QΦ) and convective heat transfer (Qs). The results demonstrate that BG30, after being enriched with 29% hydrogen and 39% oxygen, exhibits an LBV equivalent to that of BG60. The optimal convective heat transfer is achieved when the target plate is positioned slightly above the tip of the flame cone, while the optimal total heat transfer occurs when the target plate is located approximately 2/3 of the flame cone height. Based on the insights from numerical investigations, a cap-shaped target plate was tested for heat transfer from impinging flames. It effectively enhanced the total heat transfer rate on to the target plate.